CARIES RISK EVALUATION USING CARIOGRAM IN MANAGEMENT OF CHILDREN RAMPANT CARIES - Nurdiana Dewi; Siti Bale Sri Rantinah; Al Supartinah (FKG Unlam, 2018)
Background: The prevalence of rampant caries in children is still high. Management of caries should be done immediately to maintain the function of the teeth. Evaluation of rampant caries management may be performed with the cariogram. Cariogram describes the cause and sequence of caries risk. Objectives: The aim of this case report was to report the results of the evaluation of rampant caries management using cariogram in 6-year-old girls at Pediatric Dentistry Clinic of RSGMP Prof Soedomo. Method: A 6-year-old girl accompanied by her mother reported to Pediatric Dentistry Clinic of RSGMP Prof. Soedomo Faculty of Dentistry UGM with the chief complaint of multiple decayed teeth. Based on anamnesis and clinical examination, it can be concluded that the patient had rampant caries. A cariogram was performed at initial treatment, followed by DHE and topical application fluor. Treatment was performed by restore 53, 62, 63, 64, 65, 74 and 84 using Glass Ionomer Cement (GIC). Pulpectomy were performed at 75 and 85. Teeth 52 and 54 were extracted. Crown and loop space maintainer was performed to restore 55 and obtain the space of 54. Result: Evaluation of treatment using cariogram was performed at 3rd months and 6th months evaluation. Conclusion: It was concluded that there were decreased in the magnitude of caries risk factors. The highest decreased of risk factors occurred in susceptibility and bacterial factors.